Comparison of Financial Performance Before and After the Merger of PT Selamat Sempana Perkasa into PT Selamat Sempurna Tbk - Danaz Reza Marlindo; Sri Murwanti (Universitas KH. Abdul Chalim Mojokerto, 2025)
Merger is one of the strategies used for company expansion to maintain and/or develop the business. The purpose of this study is to analyze the differences in the Debt to Equity Ratio (DER), Return on Assets (ROA), Net Profit Margin (NPM), Current Ratio (CR), and Total Asset Turnover (TATO) before and after the merger of PT Selamat Sempurna Tbk and PT Selamat Sempana Perkasa. This research employs a quantitative comparative method, comparing pre- and post-merger financial data. The study uses a time series sample for a period of 2 years (2020-2022) before the merger and 2 years (2022-2024) after the merger, sourced from the official IDX website (www.idx.co.id) and the PT Selamat Sempurna Tbk website (https://smsm.co.id/). Data analysis was conducted using both the paired sample t-test and the Wilcoxon test. The paired t-test is suitable for comparing the means of normally distributed data, while the Wilcoxon test is used for non-parametric data when the normality assumption is not met. The selection of both tests ensures robustness in handling different data characteristics. The results show significant differences in the Debt to Equity Ratio (DER) and Net Profit Margin (NPM) before and after the merger. However, no significant differences were found in Return on Assets (ROA), Current Ratio (CR), and Total Asset Turnover (TATO). This lack of change in certain ratios may indicate that the merger, while impactful in terms of financial leverage (DER) and profitability (NPM), did not substantially affect the operational efficiency (TATO) or overall profitability (ROA), possibly due to the nature or scale of the merger. This study can inform policy decisions for related agencies and contribute to the development of corporate financial management, particularly in the analysis of key financial ratios such as DER, ROA, NPM, CR, and TATO.